From Reductionism Toward Integration: Understanding How Social Behavior Emerges From Integrated Circuits - Dickinson, Sarah Y.; Kelly, Diane A.; Padilla, Stephanie L.; Bergan, Joseph F. (Frontiers in Integrative Neuroscience, 2022)
Complex social behaviors are emergent properties of the brain’s many interconnected and overlapping neural networks. Questions aimed at understanding how brain circuits produce specific and appropriate behaviors have changed over the past half century, shifting from studies of gross anatomical and behavioral associations, to manipulating and monitoring precisely targeted cell types. This technical progression has enabled increasingly deep insights into the regulation of perception and behavior with remarkable precision. The capacity of these reductionist approaches to identify the function of isolated circuits is undeniable but many behaviors require rapid integration of diverse inputs. It is now possible to simultaneously observe circuit activity at multiple nodes of a network. This review examines progress in our understanding of social circuits as an example of how our understanding of brain circuits and their functions developed in conjunction with technologies for visualizing and manipulating neurons and considers how new techniques may allow us to address brain circuit function in the context of integrative and recursive anatomy.